2017
DOI: 10.5217/ir.2017.15.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xpert MTB/RIF assay performance in the diagnosis of abdominal tuberculosis

Abstract: Background/AimsThe use of genetic probes for the diagnosis of pulmonary tuberculosis (TB) has been well described. However, the role of these assays in the diagnosis of intestinal tuberculosis is unclear. We therefore assessed the diagnostic utility of the Xpert Mycobacterium tuberculosis/rifampicin (MTB/RIF) assay, and estimated the prevalence of multidrug-resistant (MDR) TB in the Indian population.MethodsOf 99 patients recruited, 37 had intestinal TB; two control groups comprised 43 with Crohn's disease (CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…However, the yield of culture and histopathology is generally quite low in GITB, which is generally a paucibacillary disease. Response to empirical antitubercular therapy or a therapeutic trial has also been considered as an important diagnostic tool in studies . To deal with these problems and to compare recent upcoming molecular methods, recent studies have used a composite diagnostic standard for the evaluation of new diagnostic tests .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the yield of culture and histopathology is generally quite low in GITB, which is generally a paucibacillary disease. Response to empirical antitubercular therapy or a therapeutic trial has also been considered as an important diagnostic tool in studies . To deal with these problems and to compare recent upcoming molecular methods, recent studies have used a composite diagnostic standard for the evaluation of new diagnostic tests .…”
Section: Methodsmentioning
confidence: 99%
“…16 To deal with these problems and to compare recent upcoming molecular methods, recent studies have used a composite diagnostic standard for the evaluation of new diagnostic tests. 16 We used similar criteria for the diagnosis of GITB. A confirmed diagnosis of GITB was made if any one of the following four criteria were met, that is, (i) histopathology of intestinal tissue showed caseating granulomas, granulomas with acid-fast bacilli; (ii) granulomatous inflammation without caseation or acid-fast bacilli (AFB) but good clinical response to antitubercular therapy (ATT); (iii) isolation of AFB bacilli in samples obtained from extraintestinal sites like sputum, resected tissues, lymph nodes, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Among the latter, the sensitivity of the Gene Xpert assay was 88% and its specificity was 91%. Kumar et al [36] found that the sensitivity, the specificity, the positive predictive value, and the negative predictive value of the Gene Xpert assay were 8.1, 100, 100, and 64.2%, respectively, in intestinal TB cases.…”
Section: Newer Diagnostic Modalitiesmentioning
confidence: 99%
“…31 Although the Xpert® MTB/Rif has emerged as an important tool for the diagnosis of pulmonary TB and some forms of EPTB (lymphadenitis), the reports on the use for ATB have indicated a limited benefit. 32 In a report on the use of Xpert in peritoneal TB, the test was positive in only 4 out of 21 patients who were diagnosed with peritoneal TB. 33 Similarly, in a report on ITB, only 3 out of 37 patients had a positive Xpert MTB/Rif test, suggesting that the sensitivity of the test for ATB would be low.…”
Section: Diagnostic Evaluation For Intestinal Tuberculosismentioning
confidence: 98%
“…33 Similarly, in a report on ITB, only 3 out of 37 patients had a positive Xpert MTB/Rif test, suggesting that the sensitivity of the test for ATB would be low. 32 The yield of an in-house PCR (using three genes: hsp-66, esat-6, and ITS MAC) was also reported to be low. 34 The bulk of evidence therefore suggests that PCR-based tests also provide a low sensitivity for the diagnosis of ATB.…”
Section: Diagnostic Evaluation For Intestinal Tuberculosismentioning
confidence: 99%